METHOD FOR SELECTING THE OPTIMAL DURATION OF OFDM SYMBOLS PREFIX IN SATELLITE COMMUNICATION CHANNELS OF AIR NAVIGATION SYSTEM - Kharchenko, Volodymyr; Odarchenko, Roman; Ismail, Ali (Proceedings of National Aviation University (archive), 2020)
To study the method of selecting the optimal duration of the prefix OFDM-symbols in satellite communication channels, the original model of the communication line "Aircraft satellite-ground station" was built. The adaptive modulation model consists of an information source, an aircraft transmitter, an uplink / downlink, a satellite transponder, and a ground station receiver. OFDM technology for combating the effects of multipath is considered. The method of combating intersymbol interference based on the use of OFDM technology has been improved.